2020
DOI: 10.1021/acsapm.0c00397
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Colorless, Highly Transparent, Epoxy-Based Vitrimers by the Thiol-Epoxy Click Reaction and Evaluation of Their Shape-Memory Properties

Abstract: Vitrimers are functional cross-linked materials with an associative bond-exchange mechanism. Here, we demonstrate the preparation of colorless and highly transparent epoxy-based vitrimers by using a simple reaction of commercially available, thiol-functionalized, and epoxy-functionalized monomers, that is, trimethylolpropane tris­(3-mercaptopropionate) (Tri-SH) and bisphenol A diglycidyl ether (di-epoxy), which can thus contribute to the practical application of vitrimers because conventional vitrimers, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…Since the pioneering series of vitrimer studies reported by Leibler’s group, various designs of vitrimers have been developed using different bond-exchange reactions. Polyester-based vitrimers with a bond-exchange mechanism via trans-esterification is one of the most reported designs for vitrimer preparation. , Trans-esterification is the reaction to exchange ester and alcohol moieties, which usually operates in the presence of catalysts. Polyester vitrimers can thus be prepared by designing networks bearing ester bonds and OH groups with addition of a trans-esterification catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering series of vitrimer studies reported by Leibler’s group, various designs of vitrimers have been developed using different bond-exchange reactions. Polyester-based vitrimers with a bond-exchange mechanism via trans-esterification is one of the most reported designs for vitrimer preparation. , Trans-esterification is the reaction to exchange ester and alcohol moieties, which usually operates in the presence of catalysts. Polyester vitrimers can thus be prepared by designing networks bearing ester bonds and OH groups with addition of a trans-esterification catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…2b, the characteristic monomer peak, epoxy peak (910 cm -1 ) in E51, and thiol peak (2566 cm -1 ) in Tetra-SH disappeared in the spectra of the vitrimers, while the hydroxyl peak (3200-3600 cm -1 ) appeared. 40,41 The FT-IR spectra of the vitrimers and ESMTW samples exhibited high similarity, indicating that a high content of vitrimers filled the porous structures of the DW scaffold. The density of the ESMTW was approximately 1.232 g cm -3 .…”
Section: Resultsmentioning
confidence: 95%
“…Recently, Christensen et al achieved closed loop recycling of a crosslinked thermoset by utilizing acid‐degradable diketoenamine bonds whereby they could isolate the triketone monomers such that the network reformed with nearly identical properties 8 . Likewise, the seminal work of Montarnal et al, who first reported on vitrimers, has inspired many research groups around the world, each developing ever so compelling chemistry to achieve these unique reprocessable networks 9–24 …”
Section: Introductionmentioning
confidence: 99%
“…8 Likewise, the seminal work of Montarnal et al, who first reported on vitrimers, has inspired many research groups around the world, each developing ever so compelling chemistry to achieve these unique reprocessable networks. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Unfortunately, many of the strategies highlighted above can prove costly with sometimes exotic and hardto-scale chemistry and often rely upon the collection of waste for further processing or composting in controlled environments. Dishearteningly, a staggering 32% of polymer-based waste escapes that very collection system and the convenience (and sometimes necessity of singleuse plastics as seen during the COVID-19 pandemic) comes in the way of ecological considerations.…”
Section: Introductionmentioning
confidence: 99%